PERAN PUSAT PELAYANAN TERPADU SERUNI SEMARANG JAWA TENGAH DALAM MEMBERIKAN PERLINDUNGAN HUKUM BAGI ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA BERBASIS NILAI KEADILAN - Ida Musofiana (Jurnal Pembaharuan Hukum, 2017)
This paper aims to assess the role of Integrated Servis Center Seruni Semarang Centra Java. This study is included in the sociological juridical study, as the researcher conducts the the research by going directly to the ﬁeld. The conseptual framework starts with the theory justice, for children who are victims domestic violence. Primary data sources consist of ﬁeld research results, while secondary data are references to bibliography related to legaprotection for child victims and related legislation. While data analysis using content analysisThe results showed that children who were subjected to violence in police handling were handled by the Woman and Child Protection Unit, but the police could refer or sent child victims to Semarang Integrated Hospital or Service Center for those domiciled in Semarang.foa child who feel trheatened his soul then lead the victim to a safe house. Integrated Service Center Seruni Semarang Central Java performs its duties in accordance with the Dercree Mayor of Semarang No.463/05/2011 on the Establishment of Integrated Service Team onHandling Violence Againts Women and Children Based on Gender “SERUNI” Semarang City Central Java.